Clinical Applications of State Alcohol Biomarkers: An update (Journal of Psychiatrists' Association of Nepal, 2022)
Alcohol Use Disorder (AUD) is one of the most prevalent causes of global burden of disease. It is associated with significant physical and mental health problems as well as social and economic consequences. Alcohol consumption is considered to be one of the most important preventable risk factors for adverse health outcomes, hence proper assessment is must for alcohol use disorder. The assessment pattern of alcohol use based on self-report of patients may not be always reliable due to recall bias and minimization highlighting the need of accurate biomarkers. In this narrative review we discuss about the different state biomarkers of alcohol, their properties and their utility in different settings during patient care. Despite many limitations traditional state markers are still useful and we recommend clinicians to familiarize themselves to use them as additional outcome measures in clinical interventions for AUDs and associated medical complications.